Median arcuate ligament syndrome noticed during pancreaticoduodenectomy - Usta, Sertac; Karabulut, Koray; Artas, Hakan (Turkish Surgical Assoc, 2022)
Median arcuate ligament syndrome (MALS) occurs as a result of compression of the celiac artery by a fibrous band called the median ligament, which originates from the diaphragmatic crus. The prevalence of MALS has been reported as 10-24% among patients. The etiology is not clear. The components of the clinical triad are a chronic post-prandial pain, epigastric murmur and weight loss. Diagnosis is based on clinical and radiological findings. MALS has been reported in a small portion of patients undergoing pancreaticoduodenectomy. Most of the patients have been diagnosed prior to surgery.
Pankreatikoduodenektomi sırasında fark edilen median arkuat ligaman sendromu
Keywords: Pancreaticoduodenectomy; median arcuate ligament syndrome; celiac artery occlusion